Knowledge hiding in academia: an empirical study of Indian higher education students. Issue 9 (24th March 2021) - Garg, Neha; Talukdar, Asim; Ganguly, Anirban; Kumar, Chitresh
Abstract : Purpose: This study aims to investigate the role of knowledge hiding (KH) on academic performance, using three antecedents – relatedness with peers, territoriality of knowledge and performance motivation. It also looked into the moderating role of academic self-efficacy upon student's KH behavior and academic performance. The research was grounded on the theory of reasoned action. Design/methodology/approachx: Structural equation modeling (SEM) was used to analyze the five hypotheses. The data was collected through a primary survey based on a structured questionnaire with a sample size of 324 students from the Indian higher education institutions. Findings: The study found that performance motivation and territoriality are positively associated with KH, which is further positively related to students' academic performance. Sense of relatedness had no influence upon KH behavior, implying that proximity of social relationships does not predict KH behavior among students. Additionally, it was also observed that while evasive (a situation where the knowledge hider deliberately provides incorrect, partial or misleading information) and rationalized KH (a situation where the knowledge hider tries to provide a rational justification for not sharing the knowledge) had a significant influence on the academic performance of the students, the effect of "playing dumb" was not significant. The study did not reveal any moderating effect of academic self-efficacy on all three forms of KH and academic performance. Practical implications: The findings of the study are expected to be valuable for instructors, administrative authorities and policymakers at the higher education level, to create a more conducive teaching and learning environment. Out of the three hiding strategies, students indulge more often in rationalized KH. Based on the outcomes of this research, management may focus toward the creation of an institutional environment conducive toward knowledge sharing interdependency among students. Originality/value: One of the novel contributions of this study is that it analyzes Indian higher education, providing a developing country perspective, thereby contributing to the body of knowledge in knowledge management and hiding. The study also intends to understand the interplay of constructs such as KH, territoriality, sense of relatedness and academic performance, which have not been discussed previously within the higher education context, thus making the research work original. The study was done among the students and hence, brings in the academic perspective in the KH literature, which has seen limited research impetus.